AKT1, PRDM4, and BAX are the natural markers of psychological endurance threshold. Issue 7 (16th May 2019) - Xu, Zhijian; Jing, Qicheng; Zhang, Houcan; Liu, Yue
Abstract: Introduction: Abnormal behavior can cause harm or loss to oneself, the family, and society and may be related to psychological endurance levels. With early identification and early intervention, the occurrence of harm can be prevented and the loss can be reduced. Now there is no clear definition of psychological endurance levels and no accurate measurement tools yet. Methods: This study first proposes the concept of psychological endurance threshold (PET) and defines that as: "the psychological state threshold of human objective physiological characteristics and outbreaks of abnormal behavior led by subjective cognitive level difference". The study hypothesizes that human behavior is related to it, and constructs multiple measurement method tools to measure it. Results: Here we show PET exists objectively and can be measured exactly by methods such as psychological endurance threshold measurement table, experience evaluation, dopamine level detection, and genetic testing. In particular, PET is determined by AKT1, PRDM4, and BAX which are the natural markers of PET. Conclusions: The significance of this study is to discover people with abnormal expression of AKT1, PRDM4, and BAX who have lower PET and tend to commit abnormal behavior more easily. Understanding PET will enable people to make self‐adjustment or to intervene by professionals as soon as possible and in a timely manner in the face of various negative stimuli in work and life, especially for people with lower PET, people should intervene as early as possible to reduce the harm to the individual, family and society. Abstract : The significance of this study is to discover people with abnormal expression of AKT1, PRDM4, and BAX have lower PET and tend to commit abnormal behavior more easily. Understanding the PET will enable people to make self‐adjustment or to intervene by professionals as soon as possible and in a timely manner in the face of various negative stimuli in work and life, especially for people with lower PET, people should intervene as early as possible to reduce the harm to the individual, family, and society.